Integrating Maqasid Shariah in Enhancing MSME Business Sustainability in the Digital Economy - Albar, Kholid; Amiruddin K; Abdullah, Wahyuddin (el-Jizya : Jurnal Ekonomi Islam, 2025)
This study aims to explore the integration of Maqasid Shariah in the measurement of Islamic business performance in the dynamic digital economy era. In this context, Maqasid Syariah, which includes the protection of religion, soul, mind, offspring, and property, offers an ethical and universal framework to guide Islamic business operations. This research focuses on Sharia MSMEs in Sidayu sub-district, which have adopted these principles in their operations. This research methodology uses a qualitative approach with a case study design. Data were collected through in-depth interviews with sharia business actors and secondary data analysis from the annual reports of relevant MSMEs. Thematic analysis was used to identify patterns and key themes related to the integration of Maqasid Sharia in performance measurement. The results showed that Sharia MSMEs in Sidayu have successfully implemented performance indicators covering spiritual, social and material dimensions. The use of digital technology, such as blockchain, is proven to increase transparency and operational efficiency, and strengthen consumer trust. The integration of technology-based and Environmental, Social, and Governance (ESG) indicators in performance measurement not only improves competitiveness but also ensures compliance with sharia principles. This study concludes that a performance measurement approach that incorporates spiritual values and modern technology can enrich the literature on Islamic business and offer practical guidance for businesses and policy makers. The implication of these findings is the need for the development of Maqasid Shariah-based performance measurement tools that can be applied more broadly, as well as further exploration in the non-financial sector to expand the application of Shariah principles in various industries